Amino acids profile for assessing Serra da Estrela cheese producers - Santos, Andreia O. (2020)
This work has the purpose to evaluate if the Serra da Estrela cheeses colletcted from 6 producers have typical chemical characteristics, with controlled variability, considering that cheeses were produced during time periods, the raw milk comes from different animals, and that the cheese processing may slightly differ between cheesemaking producers.